2005
DOI: 10.1007/s10517-005-0266-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Circulating Stromal Stem Cells with Osteogenic Potential in the Blood of Coronary Patients by Laser Flow Cytometry

Abstract: The number of cells expressing antigen to osteonectin was appreciably increased in the blood of coronary patients, but no cells of this kind were detected in donors. The number of CD34+ stem cells in these patients virtually did not differ from that in normal subjects. A close relationship between atherosclerosis development and presence of stromal stem cells with osteogenic potential in the blood is hypothesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…While novel, our findings are nonetheless consistent with recent reports by Gabbasov et al comparing circulating cells staining with an antibody for another bone-related protein, osteonectin, in patients with CAD compared with normal subjects (36,37). In those studies, osteonectin-positive cells were not characterized as EPCs; however, the authors did find that osteonectin-positive cells were increased in the circulation of CAD as compared to control patients.…”
Section: Discussionsupporting
confidence: 92%
“…While novel, our findings are nonetheless consistent with recent reports by Gabbasov et al comparing circulating cells staining with an antibody for another bone-related protein, osteonectin, in patients with CAD compared with normal subjects (36,37). In those studies, osteonectin-positive cells were not characterized as EPCs; however, the authors did find that osteonectin-positive cells were increased in the circulation of CAD as compared to control patients.…”
Section: Discussionsupporting
confidence: 92%
“…The results of proteomic studies indicated high level of stromal stem cell marker osteonectin in the blood of CA patients, which was in line with published data [1,[6][7][8][9]. High level of osteonectin-positive cells was suggested as an indicator of the presence and progress of atherosclerotic involvement of the vessels in humans [1].…”
Section: Resultssupporting
confidence: 87%
“…High level of osteonectin-positive cells was suggested as an indicator of the presence and progress of atherosclerotic involvement of the vessels in humans [1]. Low level of CD34 stem cells in patients with CHD and CA in comparison with healthy individuals can be due to intensive infuzation of these cells in zones of endothelial destruction and atherosclerotic foci [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Another potential role for the EPC from mesenchymal origin may be in determining the kind of vascular repair such as coronary calcification, with EPC that carry an osteogenic potential. 39 The extension of endothelial dysfunction may be seen in two distinct ways. On the one hand it may extend into bone marrow microvascular endothelial dysfunction (i.e., the release of EPC from the bone marrow is impaired as a result of loss of efferent vessels).…”
Section: Microcellular Endothelial Dysfunction Of Epcmentioning
confidence: 99%